La necesidad de una técnica de toma de notas en interpretación consecutiva: una experiencia - Pérez Campos, Paula; Varela Salinas, María-José (HERMES - Journal of Language and Communication in Business, 2016)
The experiment described in this paper was inspired by Daniel Gile’s Effort Model for consecutive interpreting and an experiment he conducted with students in 1991. Its goal is to determine to what extent the lack of a well-developed note-taking technique is an obstacle to optimal performance in students. The participants, a group of interpreting students who do not yet master any specific note-taking technique, are told to interpret two similar texts: one with the help of notes, one without. Their rendition is evaluated considering a series of discourse units representing different categories of markers, i.e. proper names, numbers, lists and terms. Despite the competition between the listening and analysis effort and the note production effort, all of the participants provide a better interpretation when taking notes. However, their scores show room for improvement, which could be achieved through a better command of note-taking strategies. The present work is a pilot study that paves the way for further research into note-taking in consecutive interpreting. It also highlights the importance of learning note-taking principles as part of conference interpreting training.